Voltage gating of a biomimetic nanopore: Electrowetting of a hydrophobic barrier - Sansom, M; Trick, J; Song, C; Wallace, E (American Chemical Society, 2017)
It is desirable that nanopores that are components of biosensors are gated, i.e. capable of controllable switching between closed (impermeable) and open (permeable) states. A central hydrophobic barrier within a nanopore may act as a voltage dependent gate via electrowetting, i.e. changes in nanopore surface wettability by application of an electric field. We use ‘computational electrophysiology’ simulations to demonstrate and characterise electrowetting of a biomimetic nanopore containing a hydrophobic gate. We show that a hydrophobic gate in a model β-barrel nanopore can be functionally opened by electrowetting at voltages which do not electroporate lipid bilayers. During the process of electrowetting, voltage-induced alignment of water dipoles occurs within the hydrophobic gate region of the nanopore, with water entry preceding permeation of ions through the opened nanopore. When the ionic imbalance that generates a transbilayer potential is dissipated, water is expelled from the hydrophobic gate and the nanopore re-closes. The open nanopore formed by electrowetting of a ‘featureless’ β-barrel is anionic selective due to the transmembrane dipole potential resulting from binding of Na+ ions to the headgroup regions of the surrounding lipid bilayer. Thus hydrophobic barriers can provide voltage-dependent gates in designed biomimetic nanopores. This extends our understanding of hydrophobic gating in synthetic and biological nanopores, providing a framework for the design of functional nanopores with tailored gating functionality.